JSE 33:1 Spring 2019 Editorial - Braude, Stephen (Journal of Scientific Exploration, 2019)
I’ve often noted how discussions of the evidence suggesting postmortem survival fail to consider adequately alternative interpretations in terms of dissociative processes, and in particular the apparent ease with which dissociation either facilitates the operation of living-agent psi or unleashes otherwise latent creative capacities that might suggest survival to the unwary (see, e.g., Braude 2003). I suppose it should come as no surprise that a related phenomenon sometimes occurs as well—namely, that evidence suggesting dissociative processes might in fact be evidence for the operation of psi. An interesting recent paper by Hong Wang Fung in the Journal of Trauma & Dissociation illustrates the point (Fung 2018). Hung’s paper is titled “The Phenomenon of Pathological Dissociation in the Ancient Chinese Medicine Literature.” And I commend Hung for unearthing some interesting material. He summarizes six obscure, old cases described originally in terms antedating the development of present-day psychological concepts. One case in particular stood out for me. Hung reports it as follows.